Algorithmische Hyperawareness im Songwriting von Plattform-Musiker:innen. Postdigitale Subjektivität und die Transformation musikkultureller Praktiken auf TikTok und Co. - Godau, Marc; Maxelon, Dominik; Neuhausen, Timo (Auditive Medienkulturen. ‘The Evolution of Sound’? Soundkulturelle Praktiken in Social Media-Mikroformaten)
Keywords: Algorithmen; Musikpraxis; Postdigitalität; Songwriting; TikTok

Young students’ engagement with data to create decision trees - Podworny, Susanne; Biehler, Rolf; Fleischer, Yannik (ZDM – Mathematics Education)
Abstract Statistics and machine learning are critical because they play an essential role in our everyday lives and the careers we may pursue in the future. It may be beneficial to introduce machine learning, such as decision trees (DTs), at an early stage of education. The data-based construction of DTs is an example of a machine learning process, which can be addressed in mathematics or statistics teaching because of relatively low prior knowledge requirements. This paper focuses on investigating how sixth-grade students create and evaluate data-based DTs. The basis is a teaching unit that aims to lay the foundation for machine learning and enhance students’ understanding of the process. We investigate students’ processes in detail while they build DTs with data cards about food items to predict whether a new item is recommendable. After the teaching unit, an interview study examines students’ strategies for creating decision trees. The findings contribute to understanding students’ learning processes and the challenges when working with decision trees.

Social Media Music Theory. Musiktheorie auf Instagram als Teil einer Musikpädagogik im Zeitalter der Postdigitalität - Godau, Marc; Gosmann, Phillip (Auditive Medienkulturen. ‘The Evolution of Sound’? Soundkulturelle Praktiken in Social Media-Mikroformaten)
Keywords: Edugram; Instagram; Musiktheorie; Postdigitalität; Social Media

Beyond One-Shot Explanations: A Systematic Literature Review of Dialogue-Based XAI Approaches - Mindlin, Dimitry; Beer, Fabian; Sieger, Leonie Nora; Heindorf, Stefan; Cimiano, Philipp; Esposito, Elena; Ngonga Ngomo, Axel-Cyrille (Artificial Intelligence Review)
In the last decade, there has been increasing interest in allowing users to understand how the predictions of machine-learned models come about, thus increasing transparency and empowering users to understand and potentially contest those decisions.Dialogue-based approaches, in contrast to traditional one-shot eXplainable Artificial Intelligence (XAI) methods, facilitate interactive, in-depth exploration through multi-turn dialogues, simulating expert conversations. This paper reviews the current state of dialogue-based XAI, presenting a systematic review of 1,339 publications, narrowed down to 14 based on inclusion criteria. We explore theoretical foundations of the systems, propose key dimensions along which different solutions to dialogue-based XAI differ, and identify key use cases, target audiences, system components, and the types of supported queries and responses. Furthermore, we investigate the current paradigms by which systems are evaluated and highlight their key limitations. Key findings include identifying the main use cases, objectives, and audiences targeted by dialogue-based XAI methods, and summarize the main types of questions and information needs. Beyond discussing avenues for future work, we present a meta-architecture for these systems from existing literature and outlined prevalent theoretical frameworks.

Developing a simplified linear-elastic material model for carbon paper applied in the rough rail-wheel contact - Stratmann, Ina; Hoyer, Kay-Peter; Schindler, Christian (Journal of Tribology)
Abstract The contact between two partners can be determined using experimental or numerical methods. For the validation of numerical simulations, appropriate experiments and material models of the contact partners are required. Paper in combination with carbon paper can be used in experiments to detect the area of contact between contact partners. A simplified linear-elastic material model of paper for compression in the thickness direction was developed. To evaluate the material model, it was applied to an exemplary wheel-rail contact situation.

Politik der Unpolitischen. Zur katholischen Liturgischen Bewegung in der Weimarer Republik - Adamik, Julie
Mit ihrem Werk Politik der Unpolitischen wirft Julie Adamik ein neues Licht auf die bislang traditionsgeschichtlich basierte Erforschung der Liturgischen Bewegung in der Weimarer Republik, indem sie die vernachlässigte politische Dimension dieser scheinbar unpolitischen Reformbewegung herausarbeitet. Der geschichtswissenschaftliche Ansatz und die damit verbundene umfassende Analyse der Quellen zeigen die komplexen Interaktionen zwischen den vier liturgisch bewegten Akteuren Romano Guardini, Abt Ildefons Herwegen, Abt Albert Schmitt sowie Theodor Abele und politischen Kontexten der Weimarer Republik. Dabei wird das Phänomen einer Politik der Unpolitischen untersucht, das sich im Kontext der Liturgischen Bewegung als destabilisierender Faktor der Weimarer Republik erweist. Das Buch bietet damit nicht nur neue Einblicke in das Selbstverständnis der Liturgischen Bewegung, sondern eröffnet darüber hinaus innovative Zugänge zu den Verflechtungen zwischen Religion und Politik.
Keywords: Liturgische Bewegung; Weimarer Republik; politischer Katholizismus; Romano Guardini; Reformbewegungen

A Memetic NSGA-III for Green Flexible Production with Real-Time Energy Costs & Emissions - Burmeister, Sascha Christian (Croatian Operational Research Review)

Reflexion – Repräsentation – Partizipation. Das Aufnahmeverfahren in das Bundesweite Verzeichnis des Immateriellen Kulturerbes und der Bewerbungsprozess des Schützenwesens - Leineweber, Jonas (Immaterielles Kulturerbe und Regionale Identität. Schützenwesen in Nordwestdeutschland)

Tradition im Wandel. Dynamische Tradierung und Formierung des Kulturerbes Schützenwesen in Westfalen - Leineweber, Jonas; Becker, Peter (Immaterielles Kulturerbe und Regionale Identität. Schützenwesen in Nordwestdeutschland)

Einführung - Leineweber, Jonas (Immaterielles Kulturerbe und Regionale Identität. Schützenwesen in Nordwestdeutschland)

Immaterielles Kulturerbe und Regionale Identität. Schützenwesen in Nordwestdeutschland

Fibering polarizations and Mabuchi rays on symmetric spaces of compact type - Baier, Thomas; Ferreira, Ana Cristina; Hilgert, Joachim; Mourão, José M.; Nunes, João P. (Analysis and Mathematical Physics)

Numerical modeling of clamp load relaxation of plastic nuts under varying moisture and fiber contents - Wippermann, Jan; Meschut, Gerson (Welding in the World)
This study presents a numerical approach using a 3D finite element model to quantify the remaining clamp load of a plastic nut joint after a specific time. The viscoelastic relaxation of a thermoplastic nut, which is predominantly screwed on a welding stud, is described by a material card using Prony Series. Prony Series are derived from experimental dynamical mechanical analysis with different moisture and fiber contents of the thermoplastic. Since plastic nuts usually do not have preformed threads, the increased temperatures and resulting stresses from the thread-forming process are considered in the simulation. An FE model is created and verified by substrate stress relaxation tests. Experimental clamp load measurements with miniature compression load cells verify the clamp load prediction and show a good agreement. The developed model is used to analyze the clamp load distribution within the threads and reveals an almost even distribution within the threads.

Entwicklung einer Methode für die Prognose des Anziehdrehmoments von Kunststoffmutte - Wippermann, Jan; Meschut, Gerson (JOINING PLASTICS)

Ressourceneffiziente Füge- und Entfügetechnologien: Online-Content zum interaktiven Whitepaper KORESIL - Meschut, Gerson; Gilich, Julian; Chudalla, Nick Andre (Komplexität beherrschen, Kreisläufe schließen : Soziotechnische Systeme für ressourceneffiziente Leichtbaustrukturen ; Das interaktive Whitepaper)
Die Transformation der bisher linearen Wirtschaft zu einer Kreislaufwirtschaft und einer möglichst emissionsneutralen Herstellung und Verwendung von Produkten bedarf einer ganzheitlichen Forschung und Entwicklung in allen Bereichen der Prozesskette. Die Fügetechnik gilt dabei als Enabler moderner Hybridstrukturen und ermöglicht die anforderungsgerechte Verbindung artverschiedener Werkstoffe mit unterschiedlichen technisch-wirtschaftlichen Eigenschaftsprofilen. Aktuelle Herausforderungen umfassen das qualitätsgesicherte Fügen bei einer zunehmenden Materialvielfalt aus Primär- und Sekundärwerkstoffen sowie das gezielte Entfügen von Leichtbaustrukturen in Instandsetzungs- oder Recyclingprozessen. Ein weiterer Entwicklungsschwerpunkt liegt auf der menschzentrierten Ausrichtung von Arbeitsprozessen. So können Arbeitskräfte durch eine ergonomische Produktions- und Fügeprozessplanung sowie die Entwicklung und Einbindung prozessbegleitender Mixed-Reality-Technologien gezielt entlastet und dem derzeit zu verzeichnenden Fachkräftemangel effektiv begegnet werden. Das vorliegende Whitepaper zeigt aktuelle Herausforderungen in der Fügetechnik auf, fasst relevante Erkenntnisse und Lösungsansätze aus Industrie und Forschung sowie dem Verbundforschungsvorhaben „Konzepte für die ressourceneffiziente und sichere Produktion von Leichtbaustrukturen“ (KORESIL) zusammen und leitet geeignete Handlungsempfehlungen für die Industrie ab. Diese sollen beteiligten Anwendern strategische Ansätze aufzeigen, um Prozesse ressourceneffizienter und nachhaltiger gestalten zu können.

Effects of various process parameters in the joining process on the squeeze flow of highly viscous thermal interface materials - Gilich, Julian; Teutenberg, Dominik; Meschut, Gerson; Gröger, B.; Wiebicke, F.; Koch, I.; Gude, M. (Welding in the World)
Powertrain concepts incorporating renewable energies are an essential element of the energy revolution and increasingly require efficient manufacturing processes for electronic systems. Particularly, the joining of structures to be thermally coupled, such as the battery modules and the thermal management system (TMS), poses new challenges in process design. Factors that limit the process include the increased density, viscosity, and abrasiveness of thermal pastes as well as the pressure sensitivity of battery modules. The research presented aims to systematically investigate the influences of joining parameters on flow behavior, the formation of air inclusions, and the occurring joining forces to understand and systematically optimize the joining process. Employing a test setup following the Closing-Hele-Shaw-Cell, the influence of specific process parameters on the joining process such as the joining speed, joining gap, application pattern, and temperature was investigated for a silicone- and a polyurethane-based thermally conductive paste. The results indicate a high dependency of both the ensuing joining forces and the flow behavior on the parameters investigated. These insights imply a potential systematic parameter optimization and the specific adaptation of the joining process to improve flow behavior and reduce compressive stresses. This can ensure lower component deformations and qualify the process for the employment of cell types with a higher power density, a reduced encapsulation, and lower stiffness while at the same time improving production rates.

Komplexität beherrschen, Kreisläufe schließen: Soziotechnische Systeme für ressourceneffiziente Leichtbaustrukturen ; Das interaktive Whitepaper
Im Rahmen des BMBF-Forschungsvorhabens KORESIL wurden entlang einer beispielgebenden Prozesskette für hybride Leichtbaustrukturen notwendige Forschungs- und Entwicklungsschwerpunkte ermittelt. Insbesondere die Steigerung der Ressourceneffizienz und die Unterstützung des Menschen im Kontext zukünftiger Arbeitsumfelder standen dabei im Mittelpunkt der Arbeiten. Hierauf aufbauend konnten Handlungsempfehlungen für Wirtschaft, Wissenschaft und Politik abgeleitet werden. Das Projekt KORESIL ist eingebettet in das Projektnetzwerk des Forschungs- und Technologiezentrums für ressourceneffiziente Leichtbaustrukturen – FOREL. Dieses Zentrum wurde im Jahr 2013 als BMBF-Leuchtturmprojekt eingerichtet und ist eine offene, unabhängige Plattform zur Entwicklung von Hightech-Leichtbausystemlösungen in Multi-Material-Design für die Mobilität der Zukunft. Ziel der Plattform ist die Unterstützung von Entwicklungsprojekten, die Vernetzung der Leichtbauforschung innerhalb Deutschlands und die Zusammenführung verschiedener Förderinitiativen.

Investigating the kill cloud: information warfare, autonomous weapons & AI - Bhila, Ishmael (Digital War)
The “kill chain”—involving the analysis of data by human users of military technologies, the understanding of that data, and human decisions—has fast been replaced by the “kill cloud” that necessitates, allows, and exacerbates increased thirst for domination, violence against distant populations, and a culture of experimentation with human lives. This commentary reports an interdisciplinary discussion organised by the Disruption Network Lab that brought together whistleblowers, artists, and experts investigating the impact of artificial intelligence and other emerging technologies on networked warfare. Exposing the problematics of networked warfare and the kill cloud, their colonial overtones, effects on human subjects in real life, erroneous scientific rationalities, and the (business) practices and logics that enable this algorithmic machinery of violence. The conference took place from the 29th of November to the 1st of December 2024 at the Kunstquartier Bethanien in Berlin, Germany.
Keywords: autonomous weapons systems; algorithmic warfare; cloud computing; war on terror

Effects of Early Childhood Teacher Knowledge and Feedback on Children’s Early Mathematical Development in German Kindergartens - Aumann, Lena; Puca, Rosa Maria; Gasteiger, Hedwig (Early Childhood Education Journal)
Abstract Natural everyday situations can offer valuable opportunities for children to develop mathematical ideas. However, as children enter school with widely varying levels of achievement in mathematics, not all children seem to benefit equally from embedded math learning opportunities. To help children take advantage of these opportunities, early childhood (EC) teachers seem to play a significant role in fostering children’s mathematical learning. Previous research suggests that both the teacher’s knowledge and their feedback significantly influence the extent to which children learn. However, most studies on feedback rely on experimental research designs and do not examine naturally occurring feedback in situations involving embedded math learning opportunities. Thus, the influence of EC teachers’ mathematical pedagogical content knowledge (MPCK) and their naturally given feedback on children’s mathematical learning remains underexplored. This paper investigates the effects of naturally given feedback and the MPCK of N = 48 EC teachers on the mathematical development of N = 140 children. Results indicate that process-related feedback positively impacts children’s mathematical development, while other kinds of feedback (e.g., person-related) and teachers’ MPCK do not demonstrate significant effects. These findings highlight the importance of integrating process-related feedback into professional development (PD) programs for EC teachers to enhance their ability to provide effective feedback.

Investigation of local heat treatment strategies for a multi-range capable rivet and the influence on joint formation and load-bearing capacity - Holtkamp, Pia Katharina; Kappe, Fabian; Probst, Paula; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
To reduce CO 2 emissions, the industry, particularly in the mobility sector, focuses on lightweight vehicles with multi-material structures. As thermal joining processes are reaching their limits, mechanical techniques such as self-piercing riveting are being used. One innovative solution is the versatile self-piercing riveting process (V-SPR), which combines different material combinations with a multi-range rivet. 1 The joining process is divided into the piercing process and the forming process of the rivet head to the respective sheet thickness. The rivet shaft requires sufficient strength to punch through the punch-sided sheet, and sufficient ductility of the rivet head is required to form onto the punch-sided sheet. To achieve a combination of these requirements, local inductive heat treatment strategies are used for the rivet. To ensure reproducible rivet hardening, a specialised device has been developed for precise rivet positioning in the induction coil and the subsequent quenching process. The heat treatment differs in terms of hardening times and temperatures. In addition, the heat treatment is combined with a subsequent tempering process. The study aims to determine the resulting hardness distributions and microstructures of the rivet and to investigate the influence of different heat treatment strategies on joint formation and load-bearing capacities. The results show that a graded hardening profile has a positive effect on the spreading behaviour of the rivet foot and the forming behaviour of the rivet head. Furthermore, the load-bearing behaviour of the joints is increased.